Design and development of a radial air bearing concave profile for an educational tool - Harja, Herman Budi; Febriani, Risky Ayu; Saksono, Novi; Diratama, M Yazid; Fauzi, M (Politeknik Negeri Lhokseumawe, 2025)
The increasing demand for high-speed, precision machinery has highlighted the limitations of conventional friction and anti-friction bearings, driving the need for more advanced bearing technologies, such as air bearings. However, achieving competency and skills related to air bearing components is difficult to access, particularly radial air bearing rigs. This paper presents the design of a radial air bearing rig as a learning tool to support educational objectives in understanding the working principles, use, and maintenance requirements of air bearing systems. The design stages use the VDI 2222 methodology and utilize SolidWorks for modeling. Air quality specifications refer to the ISO 9001:2015 – New Way Air Bearings standards, which consist of a fly height of 5μm, with operational parameters of 4–6 Bar input pressure and 2–13 LPM flow rate. The rig uses a single-phase motor for shaft rotation and a porous pad for air distribution. The test results show that the rig achieves a fly height of 0.5 μm at 4 Bar pressure and 5 LPM flow rate, although its rotation exhibits resistance. These outcomes confirm the rig’s potential as an educational tool and highlight the need for mechanical improvements to enhance its performance.